(untitled) (Journal of Interdisciplinary Insights, 2025)
The role of religion in communal social life and its influence on politics have demonstrated a consistent and indispensable manifestation throughout various periods of social development in the South Asian subcontinent. A century ago, amid the reconfiguration of power structures in the South Asian subcontinent, the establishment of Jama’at-e-Tabligh endowed Muslim communities with a new social role. This initiative represented both a dismantling and a reestablishment of South Asia’s rigid social hierarchy within a religious framework. It served as a timely response to addressing social fragmentation within Muslim societies following the formation of nation-states, while also balancing the elite-dominated party politics prevalent in post-colonial nation-building across the region. Implicit in these efforts of Jama’at-e-Tabligh was a political function aimed at reconciling individual-collective relationship–despite its ostensibly non-political nature. This paper is based on the research of the development of the existing historical context, through the induction of the characteristics of its development path, tries to explore the political potential contained in the organizational activities that constitute the social facts, and to further reveals the characteristics and development process of Islam in contemporary South Asia. It provides a basic research for in-depth understanding of the dynamics of South Asia, as well as the religious and political ecology.